Participación de los padres de familia en las actividades escolares y su incidencia en el rendimiento académico de los estudiantes de bachillerato, del Colegio Técnico Arenillas, sección matutina de la ciudad de Arenillas, periodo lectivo 2012-2013. - Alvarado Arequipa, MIriam Rocío (2013)
The creation of the school program for parents is important because it would help parents learn to get involved with their children's education, improving the relationship between them. Offers workshops with interesting topics, encouraging improve the role that parents in personal development of their children and why not also in their intellectual development.